Penerapan Aplikasi Padlet sebagai Sarana Pembelajaran Kolaboratif untuk Mengembangkan Keterampilan Menulis Bahasa Inggris Siswa SMP YPUI Parung - Isnaeni, Resti; Purnaninsih, Pari; Yunita, Devi (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
English writing skills are essential competencies for junior high school students in developing effective communication and academic literacy. Nevertheless, many learners face challenges in generating and organizing ideas in written form, particularly in a foreign language context. This community service–based study aims to enhance students’ English writing abilities by integrating Padlet as a collaborative digital learning tool. A qualitative approach was adopted, and the program was implemented at SMP YPUI Parung, involving 30 students and two English teachers. The findings indicate a 20% improvement in students’ writing performance as well as an increase in learning motivation. Moreover, English teachers demonstrated and enhanced skills in applying educational technology in classroom practices. The integration of Padlet proved to be an effective collaborative digital platform for improving English writing skills at the junior high school level. Keywords: Padlet, English writing skills, collaborative learning, educational technology